The role of noncoding RNAs during aortic valve stenosis. (25th November 2020) - Goody, P.R; Christmann, D; Hosen, M.R; Nehl, D; Goody, D; Niepmann, S.T; Zietzer, A; Duerr, D; Uer, O; Treede, H; Nickenig, G; Pfeifer, A; et al.
Abstract: Background: Aortic valve stenosis (AVS) is the most common valve disease worldwide. Thought to be a purely degenerative disease, it is now clear that shear stress/endothelial dysfunction, lipid deposition and inflammation lead to calcification and stenosis of the valve. There is evidence, that extracellular vesicles (EVs) are actively involved in calcification processes. Practically all cells, including endothelial cells, can generate EVs, which can be shed into the blood stream and into the interstitial space. EVs contain lipids, proteins and nucleic acids, including noncoding RNAs (ncRNAs). EVs can be taken up by acceptor cells and their cargo, especially the ncRNA content, can change the phenotype of these cells. NcRNAs have been shown to have protective and damaging properties in AVS, which can lead to disease progression. EVs are actively involved in atherosclerosis and vascular calcification, but their role during AVS formation remains largely unknown. Purpose: We hypothesize, that EV-derived ncRNAs play a crucial role during calcification of the aortic valve through regulation of endothelial to mesenchymal transition (EndMT) and calcification of valvular interstitial cells. Methods and results: In initial screening experiments, we investigated ncRNA (micro RNA, miRNA and long noncoding RNA, lncRNA) content in aortic valve tissue from explanted human aortic valves from patients undergoing surgical aortic valve replacement. There is a differential expression of miRNAs and lncRNAs in aortic valve tissue from patients with AVS and patients without AVS. We could also show a differential packaging of ncRNAs into EVs generated from patient aortic valve tissues. Furthermore, ncRNA expression in aortic valve tissue is altered in a "wire-injury" mouse model of AVS. We can demonstrate in vitro that EVs and their content can be transferred from valvular endothelial cells (VECs) to valvular interstitial cells (VICs) and vice versa. Additionally, we have established an isolation method of VECs and VICs from human samples. To identify ncRNAs involved in EndMT, we are investigating the effect of laminar and pulsatile flow on the expression of ncRNAs in vitro. We can demonstrate that different flow patterns lead to a vast change in ncRNA expression in primary VECs. Downstream effects of identified ncRNAs are currently under investigation in our in vitro calcification and EndMT models. Transfection of VICs with miRNA mimics and inhibitors and lentiviral transduction of our identified targets lead to an altered calcification potential of valve cells. Conclusion: The analysis of the cell type specific expression of ncRNAs and the intercellular communication via EVs will greatly help our understanding of the pathomechanisms leading to valvular calcification. Pathway analysis will generate new targets that could be used to develop therapeutics to ameliorate disease progression. EV-based miRNA mimics and inhibitors could be used to treat valvular calcification. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Deutsche Forschungsgemeinschaft, TRR259; Else-Kröner-Fresenius